Fracture toughness of Cu-Sn intermetallic thin films - Li, M. (2012)
Intermetallic compounds (IMCs) are formed as a result of interaction between solder and metallization to form joints in electronic packaging. These joints provide mechanical and electrical contacts between components. The knowledge of fracture strength of the IMCs will facilitate predicting the overall joint property, as it is more disposed to failure at the joint compared to the solder because of its brittle characteristics. The salient feature of this paper is the measurement of the fracture toughness and the critical energy-release rate of Cu3Sn and Cu6Sn5 intermetallic thin films, which is the result of the interaction between Sn from the solder and Cu from the metallization. To achieve the objective, a controlled buckling test was used. A buckling test in the current work refers to one that displays large transverse displacement caused by axial compressive loading on a slender beam. The stress and strain along the beam can be easily calculated by the applied displacement. Fracture-toughness values of Cu3Sn and Cu6Sn5 are 2.85 MPa √m ± 0.17 MPa √m and 2.36 MPa √m ± 0.15 MPa √m, respectively. Corresponding critical energy-release rate values are 65.5 J/m2 ± 8.0 J/m2 and 55.9 J/m2 ± 7.3 J/m2, respectively. The values obtained were much higher than the ones measured in bulk intermetallic samples but correlated well with those values obtained from conventional fracture-toughness specimens when fracture was confined within the intermetallic layers. Hence, the controlled buckling test is a promising fast and effective way to elucidate mechanical properties of thin films.